Verification of changes in the nitrate with amount of raining in drinking water of fasa;#039 s villages during years of 2007-2008 - Ebrahim Heydari kochi; Esmaeil Heydari kochi (Fasa University of Medical Sciences, 2011)
Background & Objective: Nitrate is one of the contaminants of groundwater resources that has had a growing trend in recent decades as the result of human activities such as agriculture, irregular utilization of groundwater aquifers, and non-systematic disposal of urban and industrial sewage. The increase of nitrate higher than the limit causes several health problems such as Methemoglobinemia, formation of Nitrosamine compounds and potential risks in pregnant women. Now, from among 400 wells of drinking water in Tehran, only 2 percent, that is 8 wells, have Nitrate above the limit (50mg/lit). The purpose of this study is to measure the rate of Nitrate in drinking water in rural areas of Fasa city during the years 2007 to 2008 and finding its relation with the rate of rainfall. Considering the lack of surface waters in Fasa city, almost all water requirements of the people are supplied from underground wells. Materials & Methods: This research has been conducted during the years 2007-2008. In this period, 288 samples from among 38 wells (including 24 deep well, 14 hand-made well) were selected and the rate of nitrate was measured using Espectrophotometer. Results: The obtained results indicate that in the years 2007, 2008, the maximum rate of rainfall was in winter, respectively with 94.3 and 36.6mm. and its minimum rate was in summer, respectively with 1.2 and 0.1mm, while the maximum rate of Nitrate during these years was in summer, respectively with 27.13, 27.88mg/lit and its minimum rate was in winter, respectively with 22.89 and 25.35 mg/lit. Also, the rate of rainfall in year 2007 was 168mm, which has been decreased to 57.7mm in 2008, during this period the average rate of Nitrate has been increased from 25.39 to 26.64 that this increase was more evident in hand-made wells, so that it has been increased from 37.7 in 2007 to 40.40mg/lit in 2008. Conclusion: The purpose of this study is to determine if there is any relationship between the rate of rainfall and Nitrate level in groundwater. The results of this study have shown that by the decrease of rainfall, the rate of Nitrate in the groundwater is increased in the studied region. Considering the recent drought and the decrease of atmospheric precipitations, the control of factors such as agriculture, urban and industrial sewage around wells and irregular utilization of groundwater aquifers should be considered more.